Peran Bimbingan Penyuluhan Oleh Bhabinkamtibmas Dalam Mencegah Kekerasan Seksual Pada Anak - Siburian, Fransisca Febrina (Indonesian Journal of Police Studies, 2019)
This research is backed by the high number of sexual violence in children in the law area of Cianjur Polres. The National Police of the Republic of Indonesia undertook the pre-emptive and preventive efforts of one of them through counseling guidance (binluh) in preventing child sexual violence. Therefore, research is carried out aimed at knowing the general image of sexual violence in children, the role of the Binluh by Bhabinkamtibmas in preventing sexual violence in children, as well as factors affecting the role of Binluh by Bhabinkamtibmas in preventing sexual violence in children. This research uses qualitative research approaches with analytical descriptive types. These research sources are primary, secondary, and tertiary data sources. Later, the data collection techniques used in the writing of this thesis are observations, interviews, and document studies. Furthermore, to test the accuracy and validity of data in this study using triangulation techniques. Data analysis techniques on qualitative research are data reduction, data feed, and conclusion withdrawal. Findings on the research show that the role of counseling guidance implemented by Bhabinkamtibmas is still not running with the maximum. The lack of this binary role is due to the management of activities that have not been in accordance with the existing SOP, the intensity of the binluh activities that are still lacking, the ability and qualifications of officers still do not meet the standards of existing rules, materials that are not controlled by the officers, or in terms Based on the results of the research, the authors suggest that the improvement of human resources, improving cooperation relationship with the relevant agencies, given the knowledge supply, carried out an approach to the community, as well as conducting similar research and including prevention efforts in review with different theories and concepts.